Psycho-Neuro-Endocrine-Immunological Basis of the Placebo Effect: Potential Applications beyond Pain Therapy (2022)
The placebo effect can be defined as the improvement of symptoms in a patient after the administration of an innocuous substance in a context that induces expectations regarding its effects. During recent years, it has been discovered that the placebo response not only has neurobiological functions on analgesia, but that it is also capable of generating effects on the immune and endocrine systems. The possible integration of changes in different systems of the organism could favor the well-being of the individuals and go hand in hand with conventional treatment for multiple diseases. In this sense, classic conditioning and setting expectations stand out as psychological mechanisms implicated in the placebo effect. Recent advances in neuroimaging studies suggest a relationship between the placebo response and the opioid, cannabinoid, and monoaminergic systems. Likewise, a possible immune response conditioned by the placebo effect has been reported. There is evidence of immune suppression conditioned through the insular cortex and the amygdala, with noradrenalin as the responsible neurotransmitter. Finally, a conditioned response in the secretion of different hormones has been determined in different studies; however, the molecular mechanisms involved are not entirely known. Beyond studies about its mechanism of action, the placebo effect has proved to be useful in the clinical setting with promising results in the management of neurological, psychiatric, and immunologic disorders. However, more research is needed to better characterize its potential use. This review integrates current knowledge about the psycho-neuro-endocrine-immune basis of the placebo effect and its possible clinical applications.